2016
DOI: 10.3916/c47-2016-07
|View full text |Cite
|
Sign up to set email alerts
|

Values and emotions in children’s audiovisual fictional narratives

Abstract: The aim of this study is to identify which values and emotions are transmitted in the favorite fictional TV programs of children aged between 8 and 12, according to their particular type of structure. Based on the analysis of media consumption reported by participants and their parents, as well as the ratings of children's fictional programs, two fictional programs were selected for this age group (Doraemon and Code Lyoko, with a narrative and non-narrative structure, respectively), and a content analysis of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
1
10
0
7
Order By: Relevance
“…Upon visualising the non-narrative structure, most students perceive more countervalues than they should (the percentage of students with positive residual is greater in the non-narrative structure as opposed to the narrative) and vice-versa, fewer countervalues than they should upon viewing the narrative structure (the percentage of students with negative residual is greater in the narrative structure as opposed to the non-narrative). This matches with certain works of research that observe, via content analysis, that there is a greater presence of countervalues and values in non-narrative structures (Aierbe & Oregui, 2016;Oregui, 2017). However, reception studies reveal that much fewer countervalues and values are identified in nonnarrative structures, as opposed to the narrative, and fewer countervalues than values in general (Oregui, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Upon visualising the non-narrative structure, most students perceive more countervalues than they should (the percentage of students with positive residual is greater in the non-narrative structure as opposed to the narrative) and vice-versa, fewer countervalues than they should upon viewing the narrative structure (the percentage of students with negative residual is greater in the narrative structure as opposed to the non-narrative). This matches with certain works of research that observe, via content analysis, that there is a greater presence of countervalues and values in non-narrative structures (Aierbe & Oregui, 2016;Oregui, 2017). However, reception studies reveal that much fewer countervalues and values are identified in nonnarrative structures, as opposed to the narrative, and fewer countervalues than values in general (Oregui, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…The values were categorised as: vital (e.g., playing), production (e.g., acquiring things), ethical (e.g., justice), socio-emotional (e.g., friendship), intellectual (e.g., desire to know or discover), aesthetic (e.g., beauty) and personal (e.g., self-esteem). The opposite of these means were categorised as countervalues (Aierbe & Oregui, 2016;Donoso, 1992;Oregui, 2017;Rokeach, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations